Strategi Pengembangan Wisata Bukit Di Leran Kulon, Tuban - Andarita Roalisasi (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2020)
Tuban Regency Government priority program in 2016-2021 to support the 6th strategy of the 4th mission is The Improvement and Development of Tourism Destinations. One of the potentials that can be developed in Leran Kulon Village, Palang District, Tuban Regency is a hilly area in the south. This area will optimize its natural scenery because it is one of the highest points in Leran Kulon. The research method used is qualitative narrative through literature studies and in-depth interviews. The results of this study showed that the strategy of hill tourism development in Leran Kulon is to build branding, build the participation of the surrounding community and establish the role of BUMDes (Village Owned Enterprises) as managers.